ANALISIS PENGARUH CASH POSITION, FIRM SIZE, GROWTH OPPORTUNITY, OWNERSHIP, DAN RETURN ON ASSET TERHADAP DIVIDEND PAYOUT RATIO - Satria Pribadi, Anggit; Sampurno, R. Djoko (Diponegoro Journal of Management, 2012)
This research performed to examine influence of Cash Position, Firm Size, Growth Opportunity, Ownership, and Return on Asset (ROA) on Dividend Payout Ratio (DPR). Sample for this research were taken using a purposive sampling method from manufacturing companies listed on Indonesia Stock Exchange (BEI) in period 2008 to 2011. From 134 listed companies, acquired 15 companies that meet the criteria specified in the research period from 2008 until 2011. Analyze technique that use in this research is multiple regression analysis, and hypothesis test with t test for testing the partial regression coefficient, F test for testing the simultaneously influence with level of significance 5% and determinant coefficient test. Furthermore, classical assumption test also performed including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results of this research indicate that the variable Ownership and Return on Asset (ROA) have significantly positive influence on Dividend Payout Ratio (DPR). While, Cash Position and Firm Size have significantly negative influence on Dividend Payout Ratio (DPR). Whereas Growth Opportunity hasn’t correlation influence towards Dividend Payout Ratio (DPR). It’s recommended for investors whose purpose to gain dividend, to pay more attention about information that companies spend on investment-related decisions. In this research, Return on Asset (ROA) is the most influential variable to Dividend Payout Ratio (DPR) with a standardized beta coefficient value 0,701. Predictive capability of five independent variables in this research to dividend by 43%, while other 57% were influenced by independent variables that have not been included in the research model.